Thyroid dysfunction among type 2 diabetic female Egyptian subjects - Elebrashy IN; El Meligi A; Rashed L; Salam RF; Youseef E; Fathy SA (Dove Medical Press, 2016)
Ibrahim N Elebrashy,1 Amr El Meligi,1 Laila Rashed,2 Randa F Salam,1 Elham Youssef,1 Shaimaa A Fathy1 1Department of Internal Medicine, Diabetes, and Endocrinology, 2Department of Medical Biochemistry, Faculty of Medicine, Cairo University, Giza, Egypt Purpose: High prevalence of thyroid disorders is more common in type 1 diabetes compared to type 2 diabetes, due to associated autoimmunity. Hypothyroidism is the most common disorder. The objective was to assess the prevalence of thyroid dysfunction among type 2 diabetic Egyptian females and to find the correlation between metabolic syndrome components and autoimmune thyroid dysfunction. Materials and methods: The study included 62 type 2 diabetic Egyptian females and 27 sex- and age-matched controls. All patients in the study were subjected to anthropometric measures, including HbA1c, lipid profile, serum uric acid, thyroid-stimulating hormone (TSH), free triiodothyronine, free thyroxine, anti-thyroid peroxidase (TPO), antithyroglobulin (anti-Tg), and thyroid ultrasound. Results: Hypothyroidism was found in 45.2% of patients (5.49±3.37 µIU/mL) versus 11.1% of controls (1.79±1.21 µIU/mL) (P<0.001). Anti-TPO was found in 75.8% (347.15±244.87 IU/mL) of patients versus 7.4% (32.89±33.26 IU/mL) of controls (P<0.001). Anti-Tg was found in 61.3% (508.03±369.16 IU/mL) of patients versus 0 (51.26±35.53 IU/mL) controls (P<0.001). A significant positive correlation was found between TSH and antithyroid antibodies (anti-Tg, anti-TPO; P=0.002 and P=0.043, respectively) and between TSH and thyroid-gland volume (P=0.002) in diabetic patients. No correlation was found between any components of metabolic syndrome and thyroid antibodies in diabetic patients. Conclusion: Autoimmune thyroid disease is more common in Egyptian women with type 2 diabetes than nondiabetic women, and thus points to a role of autoimmunity in the pathogenesis of type 2 diabetes. Keywords: autoimmune thyroid dysfunction, TSH, anti-TPO, anti-Tg, T2 diabetes, metabolic syndrome